Perancangan Produk Interior Modular Multifungsi Berbasis Material Kayu Olahan - Hendra Goutama; Grace Mulyono; Poppy Firtatwentyna Nilasari (Intra, 2018)
The development of variety and pattern on social activities boost the number of skyscraper as an activity center. Moreover, there is a lot of functional conversion of non-commercial to commercialize area that lead to expensive price for utilizing the area. Limited area (space) is one of the impacts of the increasing number of population in the city. Besides, technology development also builds new mindset on interior design which shifted into a medium of self-actualization. Because of the limited area, maximizing space by designing furniture is one of the solutions to resolve the problem. This design is purposed to give solution on limited space, through multifunctional modular interior product design based on processed wood material.This design concept is adopting d’school Paris Design method to details about problem, need, solution, idea, design and long-term implementation through business model canvas. These method offers few alternative design concepts as a proposed solution, regarding some aspects such as efficiency of material usage, production system, design trend, end user design taste, marketing system, distribution system, until product usage techniques. The design concept shows that multifunctional modular product based on multiplex material became a solution to solve the limited space problem in urban area. Multifunctional modular design usage has more advantages in efficiency of material usage, production system and product usage flexibility.